2016
DOI: 10.1007/s11664-016-5012-5
|View full text |Cite
|
Sign up to set email alerts
|

Probing Phase Transformations and Microstructural Evolutions at the Small Scales: Synchrotron X-ray Microdiffraction for Advanced Applications in 3D IC (Integrated Circuits) and Solar PV (Photovoltaic) Devices

Abstract: Local crystal orientation, lattice distortion and phase transformations can all be probed using submicron size x-ray beam and Laue diffraction. Fast data collection provided by state-of-the-art area detectors at synchrotron facilities and new pattern indexing algorithms optimized for speed make it possible to map large portions of a sample in a reasonable amount of time and get quantitative images of its microstructure in near real time. This technique is particularly suitable for studying the mechanical and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…is approach of using electrospinning as an additive manufacturing methodology offers the most versatile and promising technique that enables the fabrication of the hierarchical fibres even to the nanometer regimes. From the literature, both fibre structures [15,16] as well as the smaller scaled microstructures [17][18][19][20] of material have been known to lead to unprecedented materials properties, including toughness and other damage-resistant behavior [21][22][23][24][25][26]. We believe that the helicoidal structure adapts to tensile stress by allowing the plane of fibres to rotate toward or away from the applied tensile load, prolonging the final catastrophic events of failures.…”
Section: Introductionmentioning
confidence: 99%
“…is approach of using electrospinning as an additive manufacturing methodology offers the most versatile and promising technique that enables the fabrication of the hierarchical fibres even to the nanometer regimes. From the literature, both fibre structures [15,16] as well as the smaller scaled microstructures [17][18][19][20] of material have been known to lead to unprecedented materials properties, including toughness and other damage-resistant behavior [21][22][23][24][25][26]. We believe that the helicoidal structure adapts to tensile stress by allowing the plane of fibres to rotate toward or away from the applied tensile load, prolonging the final catastrophic events of failures.…”
Section: Introductionmentioning
confidence: 99%
“…Synchrotron Laue X-ray Microdiffraction (µSLXRD) is a type of X-ray Laue diffraction technique that has been used for a variety of applications for its non-destructive nature and suitability in examining the defect structure of sub-micron and nanometer scale specimens [4,7,[23][24][25][26][27][28][29][30]. The X-ray beam comes from a powerful synchrotron source, which can be focused into a submicron spot size, close to the grain size of most single crystalline materials.…”
Section: The Technique: Synchrotron Laue X-ray Microdiffractionmentioning
confidence: 99%
“…The results showed that the output power of the cells suffered from tensile residual stresses would decrease compared to the intact ones. Radchenko et al 20 conducted the stress of microelectronics devices and solar photovoltaic systems (i.e. crystalline silicon solar cells) analysis by synchrotron X-ray microdiffraction (mXRD), which showed that mXRD allows to track the evolutions in crystalline structure in the components of micro-and nanoscale devices in situ and in operando.…”
Section: Introductionmentioning
confidence: 99%
“…mXRD technology, grey-eld photoelastic technique and micro-Raman spectroscopy. As Tippabhotla 20 pointed out, mXRD technology is mostly used to study pure materials and its application in actual device is rather limited, thus the advanced applications of mXRD need to be further developed. Photoelastic technique is limit to the transparency degree of materials, and micro-Raman spectroscopy is not limited to the materials itself except the penetration depth is small.…”
Section: Introductionmentioning
confidence: 99%